Building a System to Safeguard Children in Sport: The Eight CHILDREN Pillars. (April 2017) - Rhind, Daniel J. A.; Kay, Tess; Hills, Laura; Owusu-Sekyere, Frank
In October 2014, the International Safeguards for Children in Sport were launched. These Safeguards were developed, implemented, and evaluated based on a pilot process which took place over the preceding 2 years. Throughout this piloting phase, a range of qualitative techniques were employed to capture the experiences of people within 32 of the organizations that were working toward the International Safeguards. The participant organizations varied based on their geographical focus (e.g., local, national, and international) as well as their mission (e.g., participation, competition, and sport for development). Based on a thematic analysis, eight key pillars were identified on which systems which safeguard children can be built. These are known as the CHILDREN pillars: Cultural sensitivity, Holistic, Incentives, Leadership, Dynamic, Resources, Engagement, and Networks. Illustrative examples are provided and the future directions of this project will be discussed.